INOVASI PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH PADA ERA DISRUPTIVE INOVATION MENUJU MASYARAKAT 5.0. - Syamsudin, Masagus Ilham; Misro, Misro (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract—The main focus of this research is the innovative idea of learning Indonesian in schools facing disruptive innovation in the digital era. The discussion uses critical analytics as the development of descriptive methods. The object of study is an idea or ideas. Data collection techniques used are book surveys or library research. The results of the discussion show: (1) The learning model is a conceptual framework that describes a systematic procedure in organizing experiences to achieve learning goals. The learning model is formed from the elements of focus, syntax, social systems and learning situations, and supporting factors; (2) Indonesian Language Learning is an effort to encourage students to learn the Indonesian Language curriculum which results in permanent changes in student behavior. Efforts to optimize Indonesian language learning in schools face Disruptive innovation, including: First, a paradigm shift in Indonesian Language learning is needed that is not only limited to cognitive orientation, but also the realm of psychomotor, affection and aspects of religious attitudes and behaviors. Second, Indonesian Language Learning in schools must be developed and innovated in such a way that Indonesian language learning becomes up to date and attracts students' interest. The use of information technology in the Indonesian learning model must continue to be developed and placed as a source, reference, and information on teaching materials. The use of social media in learning must also be an alternative. Including the use and use of social media for the development of Indonesian language learning in schools Keywords— Disruptive Innovation, Digital Era, Indonesian Language Learning Model Abstrak— Fokus utama penelitian  ini adalah gagasan inovatif pembelajaran Bahasa Indonesia di sekolah menghadapi disruptive innovation era digital. Pembahasan menggunakan analitis kritis sebagai pengembangan dari metode deskriptif. Objek kajian adalah gagasan atau ide. Teknik pengumpulan data yang digunakan adalah book survey atau library research. Hasil pembahasan menunjukkan: (1) Model pembelajaran adalah kerangka konseptual yang menggambarkan prosedur sistematis dalam mengorganisasikan pengalaman untuk mencapai tujuan belajar. Model pembelajaran terbentuk dari unsur fokus, sintaks, sistem sosial dan situasi pembelajaran, serta faktor pendukung; (2) Pembelajaran Bahasa Indonesia merupakan upaya mendorong peserta didik untuk mempelajari kurikulum Bahasa Indonesia yang mengakibatkan perubahan tetap dalam tingkah laku peserta didik. Upaya mengoptimalisasi pembelajaran Bahasa Indonesia di sekolah menghadapi Disruptive innovation, diantaranya: Pertama, Diperlukan perubahan paradigma pembelajaran Bahasa Indonesia yang bukan hanya terbatas pada orientasi kognitif semata, tapi juga ranah psikomotor, afeksi dan aspek sikap serta prilaku keberagamaan. Kedua, Pembelajaran Bahasa Indonesia di sekolah harus dikembangkan dan diinovasi sedemikian rupa, sehingga pembelajaran Bahasa Indonesia menjadi up to date dan menarik minat para siswa. Penggunaan teknologi informasi dalam model pembelajaran Bahasa Indonesia harus terus dikembangkan dan ditempatkan sebagai sumber, referensi, dan informasi bahan ajar. Penggunaan media sosial dalam pembelajaran juga harus menjadi alternatif. Termasuk digunakan dan dimanfaatkannya media sosial untuk pengembangan pembelajaran Bahasa Indonesia di sekolah.. Kata Kunci— Inovasi Disruptif, Era Digital, Model Pembelajaran Bahasa Indonesia